Multicentennial Agulhas leakage variability and links to North Atlantic climate during the past 80, 000 years. (18th December 2014) - Dyez, Kelsey A.; Zahn, Rainer; Hall, Ian R.
Abstract New high‐resolution sea surface temperature (SST) and sea surface salinity (SSS) estimates are presented from the Agulhas Bank slope in the Atlantic sector of the Agulhas Corridor using planktic foraminiferal (Globigerinoides ruber) δ18O and Mg/Ca‐derived SST. By focusing on the last 80, 000 years, this is the first fine‐scale Agulhas leakage record that overlaps in time with much of the Greenland ice core record of abrupt climate changes in the North Atlantic region. The multicentennial profiles indicate instances of warm SST and/or increased SSS coincident with Northern Hemisphere cool periods, followed by Northern Hemisphere warming. These periods of enhanced SST and SSS in the Agulhas Corridor occur at the last glacial termination (T1) and during North Atlantic cold episodes associated with Heinrich (H) meltwater events. To a first‐order approximation, the timing of maximal salinity events in relation to periods of North Atlantic freshwater perturbation is consistent with the concept suggested by climate models that enhanced Agulhas leakage provides for buoyancy compensation and can potentially trigger increased convective activity in the North Atlantic, thereby restoring Atlantic overturning circulation after relatively weak states.